Moving Cities - Contested Views on Urban Life (Springer Fachmedien Wiesbaden : VS, 2018)
The texts of the book focus on the problems and challenges of urban change, especially in Europe, in the contemporary context of intense mobility. The main topics are mobility, urban social structure, migrations, urban inequalities, urban activism, community, neighbourhood life, uses of public spaces and methodological approaches to urban life such as ethnography. The Content This book seeks questions and answers arising from scientific research - mainly sociological, but also in dialogue with other social sciences such as anthropology and architecture. The twelve chapters of the book introduce the reader to very different research projects developed in diverse spaces and scales. The book is a result of the work developed at the European Sociological Association Research Network 37, Urban Sociology. Target Groups Academics and researchers working in the Urban Sociology and Urban Studies disciplinary fields The general public interested in cities and urban life. The Editors Lígia Ferro is assistant professor at the Faculdade de Letras, Universidade do Porto. She is also a researcher at the Instituto de Sociologia, Universidade do Porto and at the CIES-IUL, Instituto Universitário de Lisboa, ISCTE-IUL, Portugal. Marta Smagacz-Poziemska works at the Instytut Socjologii, Uniwersytet Jagielloński in Krakow, Poland. M. Victoria Gómez is senior lecturer at the Departamento de Análisis Social, Universidad Carlos III, Madrid, Spain. Sebastian Kurtenbach, Dr, is researcher at the Institut für interdisziplinäre Konflikt- und Gewaltforschung (IKG), Bielefeld University, Germany. Patrícia Pereira is post-doctoral researcher of the Centro Interdisciplinar de Ciências Sociais, CICS.NOVA, Universidade Nova de Lisboa, Portugal. Juan José Villalón is senior lecturer of sociology at the Departmento de Sociología III (Tendencias Sociales), Universidad Nacional de Educación a Distancia, UNED, Spain.